The Effectiveness of ELC (English Language Clinic) Program to Improve Students’ Speaking Perfomance at Second Semester of English Study Program STKIP Taman Siswa Bima in Academic Year 2023/2024 - Ningsi, Fitri; Nurhidayat, Nurhidayat; Rahman, Asri (BAHTRA: Pendidikan Bahasa dan Sastra, 2024)
The problem statment in this research: was ELC (English Language Clinic) Program effective to improve students’ speaking perfomace at second semester of English Study Program.This research aimed to find out to know the ELC (English Language Clinic) Program effective to improve students speaking perfomance. This research was conducted at second semester of English Study Program Program. The researcher was a quantitative approach by applied the pre-experimental method with design of one group pre-test and post-test by compared before and after gave the treatment . Researcher used test in this research. The results of the research showed that the joint ELC (English Language Clinic) Program was effective to students speaking perfomance. Students were able to speak and fluent to explainly objects in more detail. There was a positive change from the pre-test average score of 53,53, then after gave treatment used ELC (English Language Clinic) Program it increased to 71,73. in the post-test. And from the results of the paired sample T test, it was found that the paired sample test" using SPSS, it was known that the significance value obtained was 0.000 0.05. This can be seen from the guidelines of making decision where if the value of Sig. (2- taled) 0.05 then Ho is rejected and Ha is accepted. Which means that the hypothesis in this research is accepted, it concluded that joint in ELC (English Language Clinic) program improved students speaking perfomance.This shows that the ELC (English Language Clinic) program was effective in improving students’ speaking perfomance.